Changes in Everyday and Digital Health Technology Use Among Seniors in Declining Health. (12th June 2017) - Levine, David M; Lipsitz, Stuart R; Linder, Jeffrey A
Abstract: Background: U.S. seniors' digital health and everyday technology use when their health declines are unknown. Methods: Longitudinal cohort using the National Health and Aging Trends Study, a nationally representative, annually administered sample of community-dwelling Medicare beneficiaries ( n = 4, 037). We used difference-in-differences to assess the adjusted difference (AD) in technology use from 2011 to 2014 between those with and without health declines. Health decline measures included new-onset dementia; new-onset depression; decreases in activities of daily living (ADLs), short physical performance battery (SPPB), grip strength, and self-reported health; relocation to nursing facility; increased hospitalizations; and new-onset comorbidity. Digital health included use of the Internet to research health conditions, contact clinicians, fill prescriptions, and address insurance matters. Results: Between 2011 and 2014, seniors experiencing health decline used various digital health technologies at low absolute rates (range: 1%–20%). Between 2011 and 2014, use of everyday technology decreased significantly among seniors with new-onset dementia (from 73% to 51%; AD, −26%), decreased ADLs (from 76% to 67%; AD, −10%), decreased SPPB (from 88% to 86%; AD, −3%), and relocation to a nursing facility (from 49% to 22%; AD, −31%) compared to seniors without comparable decline (all p < .05). Use of digital health decreased significantly among seniors with new-onset probable dementia (from 9% to 4%; AD, −6%) and decreased SPPB (from 24% to 25%; AD, −4%; all p < .05). Conclusions: The type of health decline a senior experiences predicts technology use, which may allow better targeting of digital health to specific seniors. Seniors with new dementia, relocation to a nursing home, and declining physical performance seem especially poor candidates for technology interventions.